Alloantigen System L Affects Antibody Responses - Medarova, Zdravka O.; Briles, W. Elwood; Taylor Jr., Robert L. (International Journal of Poultry Science, 2002)
Alloantigen system L is a polymorphic protein expressed on the surface of chicken erythrocytes and possibly certain leukocyte subpopulations. Previous studies demonstrated that the L system affects Rous sarcoma outcome and phagocytic function. The present experiments examined the L system influence on antibody responses to two antigens: SRBC (T-dependent) and Brucella abortus (BA, partially T-independent) in three B complex genotypes. The parental stock were 50% Modified Wisconsin Line 3 x White Leghorn Line NIU 4 and 50% Inbred Line 6-15.5. Pedigree matings of 4 B2B5L1L2 sires to 5 B2B5L1L2 dams per sire produced three hatches (n = 183) for the antibody response to SRBC and two hatches (n = 198) to study antibody response to BA. At 4 and 11 weeks of age the experimental birds were injected intravenously with 1 mL of 2.5% SRBC or 0.1 mL of 10% BA. Total and mercaptoethanol (ME)-resistant primary and secondary titers were analyzed by least squares ANOVA. Alloantigen L had a significant effect on total primary antibody titer to SRBC in a B5B5 background (p < 0.004) and on total (p < 0.011) and ME-resistant (p < 0.017) secondary titer to SRBC in the B2B5 genotype. Total (p < 0.004) and ME-resistant (p < 0.005) secondary titers to BA in B2B5 chickens were significantly affected by alloantigen L. The data indicate that the alloantigen L locus or genes in the immediate chromosomal vicinity affect antibody responses to SRBC and BA.